Refinements in the art of complex breast reconstruction - Bank, Jonathan (Plastic surgeon); Israeli, Ron (Elsevier, 2025)
In today's reconstructive breast surgery, what outcomes are desired by patients and what outcomes are surgically achievable? Using a case study approach, Complex Cases in Breast Reconstruction addresses the complexity of these questions in a practical, highly illustrated, and unique manner. This innovative resource uses a multimedia format to focus not only on the procedure, but on treating the whole patient. Clinical cases are presented in a series of interviews with international experts in reconstructive breast surgery, allowing readers to learn from real-world deliberations and considerations both in print and in video format. Features guided interviews with global leaders who provide personal guidance and commentary on a particular case in their area of expertise. Video interviews are accompanied by animations designed specifically for that particular case Presents each case in a highly templated, problem-based manner Covers key topics such as complications and revision surgery, breast aesthetics, failed implant reconstruction, combination flaps, abdominally-based flaps, thigh-based flaps, fat grafting, hybrid reconstruction, nerve preservation, breast pain, and more Contains an abundance of photographs, illustrations, and animations that deliver highly visual, expert guidance from the surgeon's point of view An eBook version is included with purchase. The eBook allows you to access all of the text, figures and references, with the ability to search, customize your content, make notes and highlights, and have content read aloud. Additional digital ancillary content may publish up to 6 weeks following the publication date.